Linking retail electricity pricing and the decarbonisation of the energy sector: A microeconomic approach - Linda Mastrandrea (University College Dublin, UCD School of Economics, 2021)
In this paper we address the problem of policy coordination in the electricity sector when the supply side is subject to a carbon constraint. We specifically evaluate the link between retail electricity pricing and GHG emissions reduction. Moreover, we incorporate in the analysis both the variability of electricity demand and the uncertainty of clean energy supply. By developing an analytical framework grounded in the standard microeconomic theory, we model peak pricing, block pricing and real time pricing from the perspective of a representative consumer. We then estimate the impact of each pricing scheme on the social welfare function, with a specific focus on the external cost function where GHG emissions are explicitly accounted for. We find that the impact of peak and block pricing on the carbon emissions form the electricity sector is strongly influenced by the relative emissions intensity of baseload and peak generation. In contrast, the role of real time pricing as an environmental policy tool depends on the possibility for retail customers to discriminate their consumption over the quality and price of the electricity demanded.
Keywords: Q42; D62; 330; energy economics; retail electricity pricing; greenhousegas emissions